Screening for ligninolytic enzymes from autochthonous fungi and applications for decolorization of Remazole Marine Blue - Erden,Emre (2009)
This study presents new and alternative fungal strains for the production of ligninolytic enzymes which have great potential to use in industrial and biotechnological processes. Thirty autochthonous fungal strains were harvested from Bornova-Izmir in Turkiye. In the fresh fruitbody extracts laccase, manganese peroxidase and lignin peroxidase activities, which are the principal enzymes responsible for ligninocellulose degradation by Basidiomycetes, were screened. Spores of some of the basidiomycetes species such as Cortinarius sp., Trametes versicolor, Pleurotus ostreatus, Abortiporus biennis, Lyophyllum subglobisporium, Ramaria stricta, Ganoderma carnosum, Lactarius delicious ve Lepista nuda were isolated and investigated optimum cultivation conditions in submerged fermentation for high yields of ligninolytic enzyme production. In addition, isolated fungal strains were monitored on agar plates whether having the capability of decolorization of a textile dye Remazol Marine Blue.